2023
DOI: 10.1021/acsanm.3c00630
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Synthesis of Ni3TeO6 and Cu3TeO6 Nanostructures for Magnetic and Photoconductivity Applications

Abstract: Despite great attention toward transition metal tellurates especially M3TeO6 (M = transition metal) in magnetoelectric applications, control on single phasic morphology-oriented growth of these tellurates at the nanoscale is still missing. Herein, a hydrothermal synthesis is performed to synthesize single-phased nanocrystals of two metal tellurates, i.e., Ni3TeO6 (NTO with average particle size ∼37 nm) and Cu3TeO6 (CTO ∼ 140 nm), using NaOH as an additive. This method favors the synthesis of pure NTO and CTO n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 72 publications
3
10
0
Order By: Relevance
“…The EDS mappings (Figure ) of the samples show only the presence of Cu (green), Te (blue), and O (red) elements homogeneously distributed in the sample, regardless of the morphology obtained. The relative amount obtained by EDS of the elements Cu and Te is lower (Table S1) with respect to O compared with the stoichiometric ratio (Cu 3 TeO 6 ) and our previously reported results . This fact might indicate the presence of both phases (Cu 3 TeO 6 and Cu 3 TeO 6 ·H 2 O) in the samples synthesized in this work as it was observed by XRD analysis, since the Cu 3 TeO 6 ·H 2 O material has a higher stoichiometrical amount of O in its elemental structure.…”
Section: Resultsmentioning
confidence: 37%
See 4 more Smart Citations
“…The EDS mappings (Figure ) of the samples show only the presence of Cu (green), Te (blue), and O (red) elements homogeneously distributed in the sample, regardless of the morphology obtained. The relative amount obtained by EDS of the elements Cu and Te is lower (Table S1) with respect to O compared with the stoichiometric ratio (Cu 3 TeO 6 ) and our previously reported results . This fact might indicate the presence of both phases (Cu 3 TeO 6 and Cu 3 TeO 6 ·H 2 O) in the samples synthesized in this work as it was observed by XRD analysis, since the Cu 3 TeO 6 ·H 2 O material has a higher stoichiometrical amount of O in its elemental structure.…”
Section: Resultsmentioning
confidence: 37%
“…The DRUV–vis spectra of the samples prepared at different pH values are shown in Figure b. All CTO samples showed two absorption ranges and an abrupt cutoff in the range of 200–500 nm as common in semiconductors. , The band gaps ( E g ) determined by Tauc plot analysis (Figure S5) demonstrate that the sample synthesized at acidic pH (CTO_4) had a lower band gap (2.46 eV) than the samples prepared at higher pH (CTO_6:2.6 eV, CTO_8:2.59 eV, and CTO_10:2.53 eV). The DRUV–vis results indicated that CTO is a semiconductor with a band gap in the range of the visible (2.6 eV), which is a very intriguing property for its use as a photocatalyst in visible light-mediated processes. ,, …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations